The Impact of Adopting an Eclectic Spelling Program on Minimizing KAU Engineering Students’ Spelling Mistakes - Khaled Khader Oraby; Salameh Saleem Mahmoud (LET: Linguistics, Literature and English Teaching Journal, 2023)
Competence in a certain language including correct spelling is very crucial for successful communication. Spelling mistakes may convey a totally different message and cause disastrous consequences. This study investigates the frequency of spelling mistakes in the writing of preparatory year engineering students at King AbdulAziz University. The researchers prepared three main questions related to reasons behind spelling mistakes, suggested solutions and the impact of an eclectic training program on students’ ability to minimize their spelling mistakes. They interviewed five instructors and five students and made the students write five essays about topics related to their IE200 course after receiving a training course. The findings of the study revealed determination and seriousness on the part of instructors and students to eliminate this dilemma. This was very clear in their diagnoses of the problem and their suggestions for minimizing the spelling mistakes. The study recommended giving more attention to spelling mistakes and doing more research with a bigger sample and over a longer time.